2021
DOI: 10.1371/journal.ppat.1009522
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells have divergent effects on HIV infection of initial target cells and induce a pro-retention phenotype

Abstract: Although HIV infection inhibits interferon responses in its target cells in vitro, interferon signatures can be detected in vivo soon after sexual transmission, mainly attributed to plasmacytoid dendritic cells (pDCs). In this study, we examined the physiological contributions of pDCs to early HIV acquisition using coculture models of pDCs with myeloid DCs, macrophages and the resting central, transitional and effector memory CD4 T cell subsets. pDCs impacted infection in a cell-specific manner. In myeloid cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Recently, a novel finding of HIV reactivation via IFN was reported (59) and showed that IFNa but no other IFN subtypes was able to efficiently reverse latency in both an in vitro model and in CD4 T cells collected from HIV patients on suppressive ART (59). This is similar to our recent findings of latency reversal in in vitro infected resting memory CD4 T cells (60) treated with IFNa8 or co-cultured with pDCs that secreted IFNa upon HIV exposure. Data from in vitro and humanized mice studies showed that IFNa8 and IFNa14 are more efficient at inhibiting HIV viral replication than IFNa2 (61) due to their higher affinities for the IFN receptor and the increased induction of antiviral proteins.…”
Section: Kick and Killsupporting
confidence: 92%
“…Recently, a novel finding of HIV reactivation via IFN was reported (59) and showed that IFNa but no other IFN subtypes was able to efficiently reverse latency in both an in vitro model and in CD4 T cells collected from HIV patients on suppressive ART (59). This is similar to our recent findings of latency reversal in in vitro infected resting memory CD4 T cells (60) treated with IFNa8 or co-cultured with pDCs that secreted IFNa upon HIV exposure. Data from in vitro and humanized mice studies showed that IFNa8 and IFNa14 are more efficient at inhibiting HIV viral replication than IFNa2 (61) due to their higher affinities for the IFN receptor and the increased induction of antiviral proteins.…”
Section: Kick and Killsupporting
confidence: 92%
“…Isolated CD4 + T cells (obtained as described below) were cultured at a concentration of 10 6 cells/ml in cRF10 (RPMI, Lonza) and 10% fetal bovine serum (RF10), supplemented with 1× GlutaMAX (Gibco), 100 U/ml penicillin (Gibco), and 100 μg/ml streptomycin (Gibco) in a 96-well U-bottom plate and incubated with the corresponding HIV-1 stock overnight at 37°C as previously described ( 84 ). Then, cells were washed 3 times with PBS, and cRF10 was added.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of memory CD4 + T cells to be infected with HIV-BaL and HIV-NL4-3-eGFP was performed as previously described ( 84 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on our RNAseq data obtained from activated CD4+ T cells, we analyzed cellular pathways necessary for efficient HIV-1 transcription and viral reactivation of latently HIV-1infected cells (40)(41)(42)(43)(44)(45)(46)(47). These cellular pathways include the nuclear factor kappa-lightchain-enhancer of activated B cells (NF-B), Janus kinase/signal transducer and activator of transcription (JAK-STAT), tumor necrosis factor (TNF), extracellular signalregulated kinases (ERK) and type I/II interferon (IFN) pathways (40)(41)(42)(43)(44)(45)(46)(47). We found that NF-B, JAK-STAT and type I/II IFN pathways were downmodulated in activated cells treated with TB-PE (Figure 4A-B).…”
Section: Cellular Pathways Involved In Hiv-1 Latency Are Modulated By...mentioning
confidence: 99%